Association of gestational age and growth measures at birth with infection-related admissions to hospital throughout childhood: a population-based, data-linkage study from Western Australia. Issue 8 (August 2016) - Miller, Jessica E; Hammond, Geoffrey C; Strunk, Tobias; Moore, Hannah C; Leonard, Helen; Carter, Kim W; Bhutta, Zulfiqar; Stanley, Fiona; de Klerk, Nicholas; Burgner, David P
Summary: Background: Reduced gestational age and low birthweight are associated with an increased risk of neonatal infections. However, the long-term risk of infection, especially in late preterm infants or those at near-normal birthweight, is unknown. We estimated whether rates of infection-related admissions to hospital for children in Western Australia were associated with age, gestational age, birthweight, and birth length. Methods: We did a population-based, data-linkage study using total-linked, registry data from the Western Australia Birth Register of all liveborn, non-Indigenous Australian singleton births recorded from Jan 1, 1980, to Dec 31, 2010. We followed up individuals from birth-related hospital discharge to age 18 years, death, or end of 2010, and linked to data about subsequent admissions to hospital or death registrations. Gestational age was assessed from both the last menstrual period and from estimates based on ultrasonography. We categorised birthweight by 500 g bands and birth length by 5 cm bands, and approximated the reference ranges for both to the 50th percentile. Because size at birth and gestational age are strongly associated, we calculated Z scores for gestational-specific and sex-specific birthweight, birth length, and ponderal index. Our primary outcomes were the number and type of infection-related admissions to hospital. We used multilevel negative binomial regression to generate rate ratios (RR) for such admissions, identified by codes from the International Classification of Diseases, versions 9 and 10-AM. We adjusted the RRs for maternal age at delivery, birth year, birth season, parity, sex, 5-min Apgar score, delivery method, socioeconomic status, and bronchopulmonary dysplasia. Findings: Of 719 311 liveborn singletons included in the analysis and followed up for 8 824 093 person-years, 365 867 infection-related admissions to hospital occurred for 213 683 (30%) children. Of the 719 311 children included in the analysis, 137 124 (19%) had one infection-related admission to hospital, 43 796 (6%) had two, 16 679 (2%) had three, and 16 084 (2%) had four or more. The 365 867 admissions to hospital included a diagnosis of infection of the upper respiratory tract for 174 653 (48%), the lower respiratory tract for 74 297 (20%), the gastrointestinal tract for 44 755 (12%), and a viral infection for 37 213 (10%). Infection-related rates of admissions to hospital increased by 12% for each week reduction in gestational age less than 39–40 weeks (RR 1·12, 95% CI 1·12–1·13), by 19% for each 500 g reduction in birthweight less than 3000–3500 g (1·19, 1·18–1·21), and by 41% for each 5 cm reduction in birth length less than 45–50 cm (1·41, 1·38–1·45). Gestational age-specific and sex-specific birthweight Z scores lower than the 25th to 50th percentile and birth length Z scores lower than the 10th to 25th percentile were associated with increased rates of infection-related admissions to hospital (eg, 1st–5th percentile RR 1·15, 95% CI 1·12–1·19, and 1·11, 1·07–1·14, respectively). Ponderal index Z scores lower than the 25th to 50th percentile were also associated with increased rates of infection-related admissions (eg, 1st–5th percentile RR 1·08, 95% CI 1·04–1·12). A gestational age of 41 weeks or later, a birthweight or birth length Z score above the 50th percentile, or a ponderal index Z score between the 75th and 95th percentile, were associated with modestly reduced rates of infection-related admissions to hospital. Interpretation: Children who were born with reduced gestational age, birthweight, and birth length have persistently increased rates of infection-related admissions to hospital until age 18 years. Pregnancy outcomes should be optimised to prevent infection occurring in this population, especially in resource-limited settings where suboptimum intrauterine growth and moderate prematurity are common. Funding: Australian National Health and Medical Research Council.